2005
DOI: 10.1097/01.ajp.0000173993.53733.2e
|View full text |Cite
|
Sign up to set email alerts
|

Reports of Memory Functioning by Patients With Chronic Pain

Abstract: The results support the hypothesis that emotional distress (depression and anxiety) plays an important role in memory complaints in patients with chronic pain, as well as rumination, the intrusive component of catastrophizing. Clinicians should be aware of these factors in the evaluation of memory complaints in patients with chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 36 publications
0
49
0
5
Order By: Relevance
“…Depression and intensity of bodily pain were expected to trigger the cognitive disruption in CPpatients (27,1,16). However, neither bodily pain intensity (measured by SF-36) nor depressive state (measured by SCL-90-R) were significantly related to cognitive processing.…”
Section: Depressive State and Intensity Of Bodily Pain Do Not Mediatementioning
confidence: 96%
“…Depression and intensity of bodily pain were expected to trigger the cognitive disruption in CPpatients (27,1,16). However, neither bodily pain intensity (measured by SF-36) nor depressive state (measured by SCL-90-R) were significantly related to cognitive processing.…”
Section: Depressive State and Intensity Of Bodily Pain Do Not Mediatementioning
confidence: 96%
“…In sum, the development of schemas supportive of irrational thinking impacts employee activity levels and functioning. As a consequence, the development of both work and social relationships is inhibited (Munoz and Esteve, 2005).…”
Section: Chronic Pain In Organizationsmentioning
confidence: 99%
“…Neither of these studies has investigated the utility of the MMPI-2-RF over-reporting scales in the prediction of MND among non-head injury disability claimants. Studies investigating the assessment of MND in this population are important given considerable rates of cognitive complaints found among individuals with mood and chronic pain disorders (McCracken & Iverson, 2001;Munoz & Esteve, 2005), especially because past research has shown a lack of association between subjective cognitive complaints and impaired cognitive functioning in these populations (Antikainen MMPI-2-RF AND MND 3 315 et al, 2001;Green, 2009;Suhr, 2003). Using the MND criteria we investigated mean differences among the MMPI-2-RF over-reporting Validity Scales and classification accuracies of MND at various cutoffs.…”
Section: Introductionmentioning
confidence: 99%